The impact of participation in job creation schemes in turbulent times - Annette Bergemann; Laura Pohlan; Arne Uhlendorff (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
This paper analyzes the impact of participation in job creation schemes (JCSs) on job search outcomes in the context of the turbulent East German labor market in the aftermath of the German reunification. High job destruction characterized the economic environment. JCSs were heavily used in order to cushion this development. Using data from 1990-1999 and building upon the timing-of-events approach, we estimate multivariate discrete time duration models taking selection based on both observed and unobserved heterogeneity into account. Our results indicate that after initial negative effects during the typical program duration of twelve months, probably driven by reduced job search effort during participation resulting in a rearrangement of the job queue, the impact on the job finding probability becomes insignificantly positive. Additional results, however, suggest that female and highly skilled participants leave unemployment quicker than other groups, which results in highly skilled women benefiting from participation. In general, we find no significant impact on postunemployment employment stability. Our results are robust to allowing for random treatment effects. Also taking into account endogenous participation in training programs, endogenous censoring, or multiple treatment effects do not change the results.
Keywords: C41; J64; J68; 330; Active labor market policy; job creation schemes; unemployment duration; employment stability; timing-of-events model; East Germany; transition economy; structural change